Acute recanalization of carotid stenosis is not proper: an experimental ischaemic stroke study. (20th June 2015) - Kong, Qingtao; Hafeez, Adam; Yu, Wang; Ren, Changhong; Geng, Xiaokun; Xiao, Yao; Liu, Shimeng; Zhang, Ying; Mao, Ruili; Zhou, Jiying; Ding, Yuchuan; Ji, Xunming
Abstract : Objectives: In a rat common carotid artery (CCA) stenosis model, the author determined the function of blood–brain barrier (BBB) at different time points and established an optimal time for CCA recanalization in rats with CCA stenosis combined with cerebral infarction. Methods: Common carotid artery severe stenosis combined with cerebral infarction was divided into two groups: CCA stenosis group ( n = 48) and CCA stenosis recanalization group ( n = 48). Common carotid artery stenosis recanalization was opened at time points of 1, 2, 3, 5, 7 and 14 days. Twenty-fourhours after recanalization, neurological behaviour, motor function, brain water content and immunohistochemistry of laminin and fibronectin were used to assess brain injury. The peak systolic velocity (PSV) determined by colour Doppler flow imaging (CDFI) was used to assess blood flow of the CCA. Results: In contrast to CCA stenosis without recanalization, in which severe neurological deficits and foot fault were observed at 1, 2 and 3 days, significantly less neurological deficits at 14 days and less foot fault placing at 5, 7 and 14 days were observed after recanalization ( P < 0.05). Although the brain water content was enhanced in the recanalization group at the stage of 1–3 days ( P < 0.05), a decrease in recanalization group at all time points (1–14 days) was found. Being consistent with reduced brain oedema, the expression of laminin and fibronectin gradually increased in both groups. However, at the early phase of 7–14 days (vs acute phase), the levels of basal laminar proteins were significantly ( P < 0.05) enhanced by vascular recanalization in both the ischaemic core and penumbra. Peak systolic velocity of CCA after recanalization reached the control level without stenosis. Conclusions: Our study suggests that the optimal time to open the CCA stenosis complicating cerebral infarction is at or after 7 days of CCA stenosis.